Proton Transfer Studied Using a Combined Ab Initio Reactive Potential Energy Surface with Quantum Path Integral Methodology - Wong, Kim F.; Sonnenberg, Jason L.; Paesani, Francesco; Yamamoto, Takeshi; Vaníček, Jiří; Zhang, Wei; Schlegel, H. Bernhard; Case, David A.; Cheatham, Thomas E. III; Miller, William H.; Voth, Gregory A. (Journal of Chemical Theory and Computation, 2010)
The rates of intramolecular proton transfer are calculated on a full-dimensional reactive electronic potential energy surface that incorporates high-level ab initio calculations along the reaction path and by using classical transition state theory, path-integral quantum transition state theory, and the quantum instanton approach. The specific example problem studied is malonaldehyde. Estimates of the kinetic isotope effect using the latter two methods are found to be in reasonable agreement with each other. Improvements and extensions of this practical, yet chemically accurate framework for the calculations of quantized, reactive dynamics are also discussed.